Left-right ideology as a dimension of identification and as a dimension of competition - Freire, A. (Journal of Political Ideologies, 2015)
There is some controversy about the dimensionality of the left–right (LR) distinction. Some authors argue for unidimensionality (LR structured by socio-economic issues). Other authors concede that socio-economic issues are of fundamental importance in shaping the LR divide, but nevertheless argue for multidimensionality. Considering these controversies, we define our two major goals: to test the dimensionality of LR voting alignments among the mass public in 21 countries at the individual level, and to test the differentiation of the dimensionality of the LR divide as a ‘dimension of identification’ and as a ‘dimension of competition’. Our main findings are as follows. First, as ‘dimension of identification’, LR voting has a multidimensional character: it is anchored in multiple sets of values orientations, both economic and non-economic. Second, the same cannot be said when we discuss it as a ‘dimension of political competition’: LR party-system polarization only has a significant and positive impact on left–right value voting for socio-economic values.